A,the Masalah Hukum Shalat Saat Bencana Menurut Putusan Majelis Tarjih Muhammadiyah - Muhammad Taufikur Rahman; Moh. Nurhakim; Agus Supriadi (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
This study aims to understand the importance of praying in society in any circumstances such as a disaster emergency in accordance with the guideline for the set of decisions of Tarjih Muhammadiyah. The research method this time uses a qualitative approach, the type of this research is library research. Based on the research results of the problems that occur in a disaster, especially for Muslims, they must continue to carry out the obligation to pray five times a day. From this, Muhammadiyah provides a solution on how to pray in a disaster. From this, the public knows that the important role of Muhammadiyah in solving this problem greatly affects the faith of every Muslim, why is that so? Because in a disaster emergency situation many people don't think about anything other than saving themselves. Turning to each other from here someone has faith then he will definitely think about his obligations in terms of praying five times a day. Therefore Muhammadiya provides arguments and legal basis in accordance with this situation. In accordance with the technical problems of praying during a disaster, Muhammadiyah has presented arguments for lightening prayers when a disaster occurs. So it can be concluded that there are reliefs in carrying out prayers, especially for obligatory prayers, that is, it is permissible to pray for prayers from here. Muhammadiyah can solve problems where people are confused over the arguments and legal basis regarding prayer relief in times of disaster.